Perencanaan Embung Wae Lerong untuk Pemenuhan Kebutuhan Air Irigasi di Daerah Irigasi Wae Lerong Ruteng Provinsi NTT - Denik Sri Krisnayanti; Elsy E. Hangge; Tri M.W. Sir; Eugenius Nino Mbauth; Alvine C. Damayanti (Balai Teknik Irigasi, 2020)
Wae Lerong Small dam is located in Ruteng City, Manggarai District which has a catchment area of 0,606 km2 and the annual rainfall ranges from 2,500-3,000 mm/year. But in some locations still having water shortages, so it needs rainwater harvesting to get increase agricultural potential during the dry season. This study aims to design the Wae Lerong Small dam as a rainwater reservoir during the rainy season and used in utilization to fulfill the needs of irrigation water. The method used is a quantitative method with empirical data analysis. The rainfall analysis used the Log Pearson III method and flood discharge analysis using the rational method. Evapotranspiration calculations using the Penman Modification method and the dependable discharge analysis using the F.J. Mock method. The analysis of slope stability using the Limit Equilibrium Method aided by the GeoStudio Slope / W 2007 Program. The results showed that the average monthly rainfall ranged from 28.87 - 511.99 mm/month. The rainfall for 50-year return period of 249.28 mm, and flood discharge for 50-year return period of 12.094 m3/s. The design of Wae Lerong dam is height of 13.5 m, a width of 5 m, length of 81.50 m, the upstream slope of 1:3, and downstream slope 1:2.25. For the stability of the reservoir body safety value > 1.10 so it is still in a safe condition. Wae Lerong Small dam storage capacity is 86,540.96 m3 with an inundation surface area of 19,855.69 m2 at a normal water level of 1,204.00 m. The value of dependable flow is 0.001 - 0.793 m3 /s and the water requirements for planting pattern I (Paddy-Paddy-Palawija) increase up to 0.176 m3/s. The water balance values deficit in May - September which ranged from 0.017 to 0.13 m3/s.